Training Needs for the Professional Development of Social-Studies Teachers at the Intermediate Stage in Al-Jouf in Light of Modern Teaching Trends: A Field Study - Al-Ahwal, Ahmed Said Mahmoud (اللجنة الوطنية القطرية للتربية والثقافة والعلوم, 2019)
This study is an attempt to identify the training needs of social studies teachers at the intermediate stage in Al-Jouf in light of modern teaching trends. It Focuses on the six axes of systemic planning, varied teaching strategies, information and communication technology, innovative enrichment activities in teaching, classroom-management skills, and diverse assessment methods. Its subjects are 60 male teachers and 60 female teachers carefully selected for the application of the final form of the questionnaire. It relies on 9 tables showing the cities and axes of the study, the training needs for each axis, and the analyses of findings. It finally provides a number of suggestions and recommendations for further future field studies in the Kingdom of Saudi Arabia. In other words, the present study is a kind of investigation into the training needs of the target teachers with an aim to enhance their professional development in an age characterize by its rabid change and great technological advances.
Keywords: الاحتياجات التدريبية -- التطوير المهني -- التعليم المتوسط -- أعضاء هيئة التدريس